EXPERIMENTAL STUDY ON ROTOR BALANCING AND STRUCTURAL REPAIR METHOD TO OVERCOME UNBALANCE AND STRUCUTRAL LOOSENESS IN CENTER HUNG MACHINES - Kurniawan, Andi (TRAKSI, 2024)
Unbalance and structural looseness are problems in industrial machines that can amplify the machine's vibration level if they occur simultaneously. Experimental study was done by comparing rotor balancing and machine’s structural repair methods in dealing with unbalance and structural looseness problems. The investigated equipment in this study consists of rotor and disk which represent center hung machines in industries such as fans, blowers, pumps and others. A comparison was made between the rotor balancing and structural repairs under the same initial problem conditions and vibration levels. The result of this study indicate that structural repair reduced machine vibration at higher level compared to rotor balancing. Even when the specimens were subjected to unbalance problems again, the increase in machine vibration level, which was previously improved by structural repairmen is not excessively high.